Determinación de transaminasas como aporte para el establecimiento de valores de referencia en estudiantes de unidades educativas rurales del Cantón Riobamba - Pilco Chimbo, Miguel Angel (2018)
Due to a lack of studies on value references in our social context, this research was carried out in order to determine transaminases as a contribution to reference value establishment in students from rural education units in Riobamba canton. For favoring the diagnosis of liver diseases, nowadays laboratories take into account established biological values from commercial markets, which were obtained from different samples, who took part of experiments. These referential values may vary due to various factors such as age, gender, ethnicity, socio-economic conditions, etc. The research methodology was based on a descriptive, non-experimental, cross-sectional, and field study, which was carried out on 147 students from 14 to 18 years old in the educational units of the canton Riobamba Chimborazo province. Data was gathered from a survey and a biochemical analysis of the samples for the determination of transaminases was carried out automatically in the Dimension RxL Max equipment through the application of quantitative in vitro diagnostic tests as an instrument. The concentration for TGO showed a 1% increase in high values in the male gender in relation to the female gender. The analysis of TGP concentrations does not have cases of students with high levels. Since it is specific to the liver, it can be deduced that the rural population did not present liver lesions and its sample mean according to gender did not show any variation either, the candidate population for the study of reference values corresponded to 96%.